Tribological evaluation of solid lubricant enriched in modified Jatropha-Based Oil as Minimum Quantity Lubrication (MQL) oil for composite material - Talib, N.; M. Nasir, R.; A. Rahim, E.; Lee, W. K.; Abdullah, H.; Saleh, A. (Springer, 2021)
The use of lubricant during the machining process plays an important role to reduce friction and wear. Mineral-based oil is the most widely used lubricant that provided high-quality lubrication properties. However, mineral-based oil has poor biodegradability and causes long-term pollution to the environment and harmful to human. Implementation of environmental-friendly lubricant was encouraged to achieve sustainable manufacturing practices. The inherent biodegradability of vegetable-based oil with solid particle offers greater benefit to the environment and lubrication performance. The study aims to evaluate the influence of green solid particle (hexagonal boron nitride, hBN) enriched in the modified jatropha oil (MJO) through tribology testing using four-ball tribotestermachine. hBN particlewas added inMJOat various concentration ratio; 0.05wt% and 0.5wt%. TheMJOsamples were compared with the crude jatropha oil and commercial synthetic ester. The tribology testing was conducted according to ASTM D4712. The value of coefficient of friction, wear scar diameter, worn surface analysis and surface roughness were evaluated. The lowest concentration of hBN particles in MJO (MJO + 0.05 wt% hBN) has reduced the coefficient of friction with smaller wear scar diameter and better surface roughness quality. The worn surface analysis from the ball lubricate byMJO + 0.05 wt% hBN had light and shallow grooves. The study proved that MJO + 0.05 wt% hBN exhibits better lubrication ability and suitable as an alternative for the environmental-friendly lubricant especially for minimum quantity lubrication (MQL) oil.